Implementation of the Equivalency Education Program by the Department of Education for Correctional Inmates at the Class IIB Correctional Institution of Lamongan Regency - Kaheesha Zalfa Rohadatul ‘Aisy; Indah Prabawati; Tjitjik Rahaju; Tauran T (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the implementation of the Equivalency Education Program by the Lamongan Regency Education Office for Correctional Inmates at the Class IIB Lamongan Prison as an effort to fulfill the right to education. This study uses a qualitative descriptive approach with data collection techniques through interviews, observation, documentation, and literature studies. The analysis of this study uses the George C. Edward III policy implementation model which includes indicators of communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of the Equivalency Education Program has been running quite well on the disposition and bureaucratic structure indicators. However, in the communication aspect, obstacles are still found in the form of unclear and inconsistencies in the learning schedule which impacts the effectiveness of the learning process for inmates. In addition, in the resource aspect, there are still limitations in human resources, especially the number of Equivalency Education tutors who are not sufficient. Therefore, it is necessary to strengthen the clarity and consistency of communication regarding scheduling and improve human resources to support the successful implementation of the Equivalency Education Program at the Class IIB Lamongan Prison.